Pengaruh Massa Dan Ukuran Partikel Adsorben Kulit Singkong Terhadap Efisiensi Penyisihan Fe Pada Air Gambut - Afmarenti, Winda; Daud, Syarfi; Andesgur, Ivnaini (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Peat water is surface water are blackish brown and metals Fe which requires effective and efficient processing to be worthy for use by the public. Various types of adsorbents continue to be developed, one of which is the cassava skin adsorbent. Thepurpose of this study was to determine metal removal efficiency of Fe in the peat water, calculating the adsorption capacity and determine the appropriate type of isotherm. Fixed variables used in this study is the stirring speed of 100 rpm and acontact time of 60 minutes. For independent variables used consisted of adsorbent mass variation of 0.5; 1; 1.5; 2 g and a particle size variation -50+100; -100+170 and -170 mesh. Removal efficiency of Fe metals concentrations higher 75,46% by mass of adsorbent 2 g with a particle size of -170 mesh. Metal adsorption capacity of Fe achieved the highest on the mass of 0.5 grams with a particle size of -170 mesh amounted to 0,2928 mg Fe/g. Types of adsorption isotherms corresponding to Fe by cassava skin adsorbents is Freundlich isotherm with R2 values of 0.9508.Keywords: Adsorbent, Adsorption, Cassava Skin, Fe, Peat Water.